Eucoleus contortus (Nematoda: Capillariidae), a parasite of Cairina moschata domestica (Anseriformes: Anatidae) on Marajó Island, Pará State, in Brazilian Amazon - Carvalho,Elaine Lopes de (2019)
Abstract The family Capillariidae is one of the most important in the superfamily Trichinelloidea, with 27 genera and more than 300 species parasitizing vertebrates. This study considers the morphology, morphometry and prevalence of Eucoleus contortus parasitizing the Muscovy duck Cairina moschata domestica esophagus from Marajó Island, in State of Pará, Brazil. Morphologically the nematodes had a filiform body, with transversely striated cuticle, long esophagus, divided into two parts, one muscular and another consisting of stichocytes, spicule weakly sclerotized, spiny sheath and pseudobursa present in males. Females had a pre-equatorial vulva, barrel-shaped eggs and were bioperculated. In the northern region of Brazil, the Muscovy duck is an abundant bird, and one of the items in the food supply for human communities. The occurrence of E. contortus adds data to the biodiversity of parasites described in Anseriform birds of the Brazilian Amazon, especially those used as source of protein by human communities of Marajó.